Sustentabilidade nas normas para edificações habitacionais: uma análise da ABNT NBR 15575 - desempenho, com o International Residential Code (IRC) - Maria Aparecida de Oliveira Miranda (2017)
The technical standard ABNT NBR 15575 Residential Buildings - Performance, which took effect in July 2013, has faced some obstacles to its implementation. The objective of this study is, through a comparative analysis with the International Residential Code (IRC), used in several US States; with a focus on the sustainability of buildings. The method used was descriptive and documentary research, with the use of technical standards cited, the NBR 15575 and IRC. The comparison results show that the NBR 15575 is a tool with a great potential to provide new residential buildings with higher quality and performance, but it has barriers for its proper implementation. Barriers such as inadequate training of project planners; lack of planned and systematic supervisions at the construction sites; besides the semi-industrialized or even still handcrafted building methods in Brazil. It appears that new construction of residential buildings require careful monitoring through periodic inspections that can verify the satisfaction of all items required by the NBR 15575 and other standards. The results indicate the sustainability requirements and by NBR 15575 (2013) - durability, maintainability and environmental adequation - are also required by IRC (2012) dealing with the same requirements in their systems for the construction of residential buildings, although not explicitly in the text of Brazilian standard, which devotes a topic only for the subject. It is considered that both standards - both the US, as the Brazilian standard - still has a lot to evolve in relation to sustainability, not least because the subject is still in development, due to the many adjustments you need to do to enable the continuity of life on the planet, by reducing consumption, recycling and reuse of materials, recycling and proper disposal of waste, among many other aspects. Therefore, it is necessary to consider this issue as an open issue that should be on the agenda for new and ongoing research in order to deepen the theme and bring new solutions and perspectives to make all kinds of buildings, and mainly a residential buildings, yet more sustainable.